AVALIAÇÃO CEFALOMÉTRICA DO ESPAÇO AÉREO NASO E BUCOFARÍNGEO E SUA IMPORTÂNCIA SOBRE O PADRÃO DE CRESCIMENTO E FUNÇÃO RESPIRATÓRIA EM INDIVÍDUOS COM MÁ OCLUSÃO CLASSE II, DIVISÃO 1 DE ANGLE - Almeida, Luciano Pacheco de (2005)
The purpose of this study was to evaluate the size of nasal and oral air pharyngeal space in subjects with Class II, division 1 Angle malocclusion. The method used to measure the nasal and oral air space of 122 lateral cephalometric X rays in white Brazilian subjects with interval age of 12 to 21 years old. Among this group, 62 presented nasal and 60 oral breath and none undergone to previous orthodontic treatment. The results showed no gender differences; the nasal breath individuals presented wider size of upper and lower limits and narrower transverse section of air space when compared to oral breath ones. The mean adenoid size was larger in oral breath patients. There were no differences between the variables analyzed when compared with facial patterns. Therefore, when facial pattern was associated with breath type it was found large proportion of oral breath subjects with vertical and norm facial patterns in relation to horizontal facial patterns.